Efficient electroluminescence from twistacene-modified π-conjugated compounds. (June 2020) - Tian, Feng; Wang, Tao; Dang, Wei; Xiao, Jinchong; Zhao, Xiaohui
Abstract: Twistacene-modified π-conjugated compounds usually possessing perfect molecular structure and tailorable optoelectronic property can decrease intramolecular and intermolecular π-stacking to a certain extent. Meanwhile, these branched macromolecules might be chosen as active layers for organic electronics. Following this direction, we design and synthesize two novel dendrimer compounds 1 and 2 . Both of them emit strong blue and green fluorescence in organic solvents and thin film with high quantum yields. The fabricated OLED devices based on them showed the maximum brightness of 982 cd m −2 for device-1 and 20801 cd m −2 for device-2. Graphical abstract: Two novel twistacene-modified π-conjugated compounds containing mismatch structures exhibit promising electroluminescence. Image 1 Highlights: Two novel π-conjugated compounds with mismatch structures have been synthesized. Both of them emit strong blue and green fluorescence in organic solvents and thin film. The optimized devices with these compounds as emitters exhibited excellent electroluminescent performance.